Measuring Entrepreneurial Skills with Digital Literacy and Entrepreneurship Literacy as Mediators (A Study of Vocational High School Students in Blitar Regency) - Suprianto, Agus; Cipto Wardoyo; Satia Nur Maharani (International journal of technology and education research, 2025)
This study aims to analyze the effect of entrepreneurship education on the entrepreneurial skills of vocational high school students, taking into account the role of digital literacy and entrepreneurship literacy as mediating variables. This study uses a quantitative approach with a survey method through hypothesis testing. The research sample involved 223 12th grade vocational high school students in Blitar Regency. Data analysis was conducted using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results of this study indicate that entrepreneurship education does not have a significant or negative effect on entrepreneurial skills. This occurs because the entrepreneurship education process applied to students is more theoretical, lacks practical application, and the material is not aligned with students' needs in the workplace. Meanwhile, entrepreneurship education can have a significant and positive impact on digital literacy and entrepreneurship literacy. These results indicate that entrepreneurship education can enhance students' skills in using digital technology. Entrepreneurship education serves as the foundation for digital knowledge and entrepreneurial understanding, enabling students to create businesses in the future. The implications of this study are highly useful for developing policies, business practices, and approaches that enhance the entrepreneurial skills of vocational high school students in Blitar Regency